2017
DOI: 10.20452/pamw.4001
|View full text |Cite
|
Sign up to set email alerts
|

Current management of gout: practical messages from EULAR 2016 guidelines

Abstract: REVIEW ARTICLE Current management of gout: practical messages from 2016 EULAR guidelines 267 where these differ significantly from the earli er guidelines and other recent national and in ternational recommendations for the manage ment of gout.Why do we need updated recommendations? There were at least half a dozen good reasons why the EULAR recommendations needed to be up dated in 2016. 1 Knowledge of the pathophysiology of uric acid (UA) transport, urate crystal inflammation, and the comorbidities associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 43 publications
2
30
0
2
Order By: Relevance
“…The British Society for Rheumatology recommends use of oral and/or intraarticular corticosteroid for patients who cannot tolerate NSAIDs (135). Furthermore, despite lack of evidence, the 2012 ACR Guidelines for Management of Gout and 2016 EULAR Guidelines include use of intraarticular corticosteroid injection as an option for first-line therapy (136), without an established recommended dose. Oral steroids are preferred if the gout involves more than 2 joints (127).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The British Society for Rheumatology recommends use of oral and/or intraarticular corticosteroid for patients who cannot tolerate NSAIDs (135). Furthermore, despite lack of evidence, the 2012 ACR Guidelines for Management of Gout and 2016 EULAR Guidelines include use of intraarticular corticosteroid injection as an option for first-line therapy (136), without an established recommended dose. Oral steroids are preferred if the gout involves more than 2 joints (127).…”
Section: Discussionmentioning
confidence: 99%
“…A serum uric acid level <6.0 mg/dL is generally recommended as an initial target in hyperuricemia therapy (92,95). sUA below this level has been associated with a reduced frequency or prevention of gout flares (92,136,137). Lower serum urate level (<5.0 mg/dL) may be needed for some patients with more severe disease (137).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of allopurinol as an inhibitor of XO was aimed at increasing the half‐life of the anti‐leukemic drug; however, it was found that the combination therapy of mercaptopurine/allopurinol did not improve the efficacy of the anti‐leukemic drug. Allopurinol was subsequently investigated for its inhibitory activity against XO and was approved by the US Food and Drug Administration (FDA) in 1966 for the treatment of gout, and is currently still the drug of first choice in the treatment of hyperuricemia as advised by the 2016 European League Against Rheumatism (EULAR) guidelines …”
Section: Purine‐based and Purine‐like Inhibitors Of Xomentioning
confidence: 99%
“…Hyperuricemia has been defined as serum uric acid (UA) ≥ 7mg/dL in men and ≥ 6mg/dL in women according to the European League Against Rheumatism Guide (EULAR) [10].…”
Section: Experimental Partmentioning
confidence: 99%